ACTIVE FILTER PERFORMANCE IMPROVEMENT ON SINGLE-PHASE RECTIFIER CONTROLLED BY USING PULSE WIDTH MODULATION (PWM) - Sudirman Syam; Sri Kurniati (Universitas Nusa Cendana, 2023)
Various commutation techniques, such as forced commutation, ignition angle control, and symmetrical angle control, have been developed to improve the input power factor and harmonic level. However, all of these techniques will produce only one pulse per half cycle of the converter input current, and consequently, the lowest order harmonic is the third harmonic. A comparative study of active filter converters between single pulse and PWM control has been investigated. Both converters are given identical R and RL loads to compare power factor (PF) and Total Harmonic Distortion (THD). The method used is a simulation with the PSPICE program. The performance of both rectifiers is evaluated based on the input current waveform, THD, and PF. At RL load, the input current distortion decreases drastically, with a THD of 100.67%. In PWM control, harmonics are reduced with a THD of 25.48%. The rectifier power factor in the active filter obtained PF of 0.25, whereas in PWM control, PF increased by 0.65.